Normobaric hypoxia increases the growth hormone response to maximal resistance exercise in trained men. Issue 7 (9th August 2017) - Filopoulos, Dean; Cormack, Stuart J.; Whyte, Douglas G.
Abstract: This study examined the effect of hypoxia on growth hormone (GH) release during an acute bout of high-intensity, low-volume resistance exercise. Using a single-blinded, randomised crossover design, 16 resistance-trained males completed two resistance exercise sessions in normobaric hypoxia (HYP; inspiratory oxygen fraction, (FiO2 ) 0.12, arterial oxygen saturation (SpO2 ) 82 ± 2%) and normoxia (NOR; FiO2 0.21, SpO2 98 ± 0%). Each session consisted of five sets of three repetitions of 45° leg press and bench press at 85% of one repetition maximum. Heart rate, SpO2, and electromyographic activity (EMG) of the vastus lateralis muscle were measured throughout the protocol. Serum lactate and GH levels were determined pre-exposure, and at 5, 15, 30 and 60 min post-exercise. Differences in mean and integrated EMG between HYP and NOR treatments were unclear . However, there was an important increase in the peak levels and area under the curve of both lactate (HYP 5.8 ± 1.8 v NOR 3.9 ± 1.1 mmol.L −1 and HYP 138.7 ± 33.1 v NOR 105.8 ± 20.8 min.mmol.L −1 ) and GH (HYP 4.4 ± 3.1 v NOR 2.1 ± 2.5 ng.mL −1 and HYP 117.7 ± 86.9 v NOR 72.9 ± 85.3 min.ng.mL −1 ) in response to HYP. These results suggest that performing high-intensity resistance exercise in a hypoxic environment may provide a beneficial endocrine response without compromising the neuromuscular activation required for maximal strength development.